Relationship between longitudinal changes in skeletal muscle characteristics over time and functional recovery during intensive rehabilitation of patients with subacute stroke. Issue 5 (4th July 2022) - Tanaka, Shu; Ito, Daisuke; Kimura, Yosuke; Ishiyama, Daisuke; Suzuki, Mizue; Koyama, Shingo; Narita, Yuya; Masuda, Hiroaki; Suzukawa, Katsumi; Yamada, Minoru
ABSTRACT: Background: Stroke is a disease that easily impairs skeletal muscle characteristics, resulting in low quantity, low quality, and poor strength. However, the recovery process of skeletal muscles in patients with stroke is not well established. Objectives: We aimed to determine the longitudinal changes in skeletal muscle characteristics in patients with stroke during intensive rehabilitation and examine their relationship with functional recovery. Methods: Eighty-five patients with stroke were prospectively recruited. We defined muscle quantity and quality as ultrasonographic muscle thickness and echo intensity, respectively, and muscle strength as knee extension strength. These skeletal muscle characteristics were compared at four time points: on admission, after 2 weeks, after 4 weeks, and at discharge. We also explored the relationship between changes in skeletal muscle characteristics and functional recovery. Results: Non-paretic knee extension torque (F = 5.838, P = .001), paretic quadriceps thickness (F = 2.943, P = .039), and paretic tibialis anterior thickness (F = 4.654, P = .004) improved over time, and changes in the paretic side quadriceps thickness were significantly associated with recovery for balance ability (odds ratio, 1.05; 95% confidence interval, 1.00–1.09; P = .048). Conclusions: The present study revealed that knee extension muscle strength on the non-paretic side and quadriceps and tibialis anterior thickness on the paretic side significantly improved over time and that changes in the paretic side quadriceps thickness were associated with the recovery of balance ability.